Kualitas Pelayanan e-KTP di Dinas Kependudukan dan Pencatatan Sipil Kota Bogor - Naila Lutfia Agustari; Salsabila Rahmadina; Firda Febriyanti; Abdul Rahman (Universitas Maritim AMNI Semarang, 2024)
The Bogor city population and civil registration service program application is the Population Administration Information system (SIAK) application. This includes e-ID services, family cards and birth certificates. The functioning of the Online KTP Registration application not only makes things easier for Bogor City residents. This application is also an additional public facility that supports efforts to make Bogor City a Smart City. In an effort to utilize information technology in providing population document services to the community with the aim of making it easier, simplifying the system and ensuring transparency, the Bogor City Population and Civil Registration Department is collaborating with all SKPD as a basis for development planning by utilizing a population database. The problem with the new system is that the e-KTP service in the city of Bogor is not yet optimal. Because there are still many people who have difficulty using this application and not all people know the procedures. Apart from that, there are also system response problems caused by slow internet networks, slow responses and lack of availability of blanks. The method in this research is a qualitative approach and uses a literature study or literature review method. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials (Kartiningrum 2015). To find out the quality of service in this research, theoretical indicators according to Zaithhanl are used, such as Tangible, Reliability, Responsiveness, Assurance, and Empathy.